STATISTICS WITH SPSS FOR RESEARCH - Tay, Choo Chuan; Muhamad, Mohd Razali; Tam, Cai Lian; Sek , Yong Wee; Asmai, Siti Azirah (UTeM, 2011)
This book consists of five chapters: Correlation, Regression, t – Test, ANOVA and Crosstabs Procedure with worked examples and review exercises. For the purpose of helping students to master the skills of this subject, step by step easy approach has been designed and adopted by the authors of this book. This is deemed as the best approach when the design of the content is structured and well-organized. Furthermore, a large part of the syllabus involves the mastery of manual mathematical calculation and step by step, direct instruction is the best approach in order to obtain an answer. In addition, for students who are not so good in math-logic reasoning and dealing with numbers, this method may enable them a sure way of obtaining the correct answer by following a set of given guidelines. Assessment is the process of evaluating the extent to which students have developed their knowledge, understanding and abilities. It involves determining what does the student know, understand, and can do with the knowledge gained from the lessons. For the purpose of evaluating whether the students have achieved the objectives of the chapters, exercises in form of assessments based on theory was used. In order to maximize the student’s learning capability, the authors took effort in providing extra exercises that cover the manual calculation and SPSS calculation for all different chapters. The Step by Step Leaning SPSS would also work as a good guide book that enhance the level of understanding of the concepts and enable students to execute the appropriate steps in coming up with the correct interpretation.